2008
DOI: 10.1507/endocrj.k07e-125
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Endothelial Dysfunction in Acromegaly after Transsphenoidal Surgery

Abstract: Abstract. Flow-mediated vasodilatation (FMD) is a vascular functional test to detect endothelial dysfunction at the early stage of cardiovascular diseases. Patients with active acromegaly have higher morbidity and mortality due to cardiovascular events. To determine whether active acromegaly is associated with endothelial dysfunction, we studied 17 patients with active acromegaly for measurements of FMD, carotid intima-media thickness (IMT) and brachial-ankle pulse wave velocity (baPWV), and other biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
0
31
1
2
Order By: Relevance
“…Smith et al (12) observed an increased augmentation index (a measure of arterial stiffness) in 16 NOR-ACRO, when compared with healthy controls, with a partial reduction after 3 months of GH suppression therapy. Sakai et al (13) reported no change in pulse wave velocity (a different measure of arterial stiffness) in patients with active acromegaly after transsphenoidal surgery, despite improved endothelium-mediated dilation. More recently, Paisley et al (14) reported a significantly increased pulse wave velocity but unaltered intima-media thickness in 56 patients with acromegaly when compared with controls, considering this phenomenon as a pressure-related stiffening of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al (12) observed an increased augmentation index (a measure of arterial stiffness) in 16 NOR-ACRO, when compared with healthy controls, with a partial reduction after 3 months of GH suppression therapy. Sakai et al (13) reported no change in pulse wave velocity (a different measure of arterial stiffness) in patients with active acromegaly after transsphenoidal surgery, despite improved endothelium-mediated dilation. More recently, Paisley et al (14) reported a significantly increased pulse wave velocity but unaltered intima-media thickness in 56 patients with acromegaly when compared with controls, considering this phenomenon as a pressure-related stiffening of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on arterial stiffness in acromegaly, all using pulse wave analysis, with contrasting results (12,13,14). The aim of our study was to investigate arterial stiffness using the ambulatory arterial stiffness index (AASI) and symmetric AASI (Sym-AASI), two indexes derived from 24 h ambulatory blood pressure monitoring (ABPM) (15,16), in a group of normotensive and hypertensive patients with active acromegaly, compared with normotensive controls (NOR-CTR) or hypertensive controls (HYP-CTR).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that flow-mediated dilatation and endothelial cell markers were significantly lower in uncontrolled and also controlled acromegaly patients than healthy subjects [2,21]. In another study, it was also shown that impaired carotid intima-media thickness and brachial-ankle pulse wave velocity could persist after transsphenoidal surgery [22]. Present study showed that although the levels of SOD and TAC were higher in controlled acromegaly patients than those with uncontrolled disease activity, uncontrolled and also controlled acromegaly patients had the decreased levels of SOD and TAC compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Since the authors did not present data analysis separately for men (nZ65) and women (nZ35), it cannot be excluded that the observed association of IGF1 levels and acetylcholine-induced forearm blood flow in their whole population was due to the preponderance of male subjects. Other studies focussing on the relationship of serum IGF1 levels and endothelial function were even smaller and primarily confined to patients with disturbed GH secretion, such as acromegaly or GH deficiency (15)(16)(17). In patients with low (15,16) and high (17) preinterventional serum IGF1 levels, normalization of IGF1 levels led to an improvement of previously reduced FMD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with low serum IGF1 levels due to GH deficiency, substitution of GH leads to normalization of a previously reduced FMD (15,16). On the other hand, in acromegaly patients with high IGF1 levels, surgical resection of the GH-producing tumor was followed by an improvement of previously reduced FMD (17). More recently, an association between serum IGF1 levels and the acetylcholine-stimulated increase of forearm blood flow, as measured by plethysmography, was described in a population of 100 untreated hypertensive patients (18).…”
Section: Introductionmentioning
confidence: 99%